Age, player position and 2 min suspensions were associated with match injuries during the 2017 Men`s Handball World Championship (France) - Tabben, M.; Landreau, P.; Chamari, K.; Juin, G.; Ahmed, H.; Farooq, A.; Bahr, R.; Popovic, N. (British Journal of Sports Medicine, 2019)
Aim: To study the association between player characteristics, technical components of the game and the risk of match injuries during the 2017 Men`s Handball World Championship.